PELAKSANAAN SISTEM PENGUPAHAN TERHADAP TENAGA KERJA WANITA PADA PERUSAHAAN PEMBORONG BANGUNAN DI DENPASAR - SUKERTI, NI NYOMAN; PURWANTI, NI PUTU (Jurnal Studi Jender SRIKANDI; Vol. 3, No. 2 Juli 2004, 2012)
This article will be focused on the discussion about waging system to daily labour women at building contractor company in Denpasar. As daily labour women, they work eight hours a day, sometimes added by overtime and no weekend holiday. This research found that from the waging system, the contractor do not conduct discrimination in remunerating to woman labour. Thereby hence the rule of regulation number 25, 1997 section 113 articles 2 have been applied effectively. It seems that the entrepreneur have known and comprehend about regulation going into effect. As entrepreneurs they prefer to employ women in certain works like at traditional ritual field because their earning will increase. It can be concluded that there is no discrimination to women labour conducting by the contractor in waging system in Denpasar.
Keywords: Sistem pengupahan, tenaga kerja wanita, perusahaan pemborong bangunan.